Nursing management of a patient with Pneumocystis carinii pneumonia after combined liver and kidney transplantation (1例肝肾联合移植术后并发卡氏肺孢子菌肺炎患者的护理体会) - JU Xingxing (居星星); YU Rui (于瑞) (中西医结合护理)
This paper summarized the nursing management of a patient with Pneumocystis carinii pneumonia after combined liver and kidney transplantation. Key issues of nursing included medication care, intake/output management, targeted treatment support, prevention of infection, psychological care, and so on, aiming to improve the prognosis of disease by early diagnosis, timely intervention and whole-process treatment. (本文总结1例肝肾联合移植术后并发卡氏肺孢子菌肺炎(PCP)患者的护理经验, 包括用药护理、液体及出入量管理、对症支持治疗、预防感染、心理护理等, 通过早期发现、及时干预、全程治疗, 对促进患者预后有积极作用。)